Effect of nutrition, harvesting date and fruit canopy position on yield and quality of Kinnow mandarin (Citrus nobilis x Citrus deliciosa) - THAKRE, MADHUBALA; VERMA, M K; SINGH, K; AWASTHI, O P; VERGHESE, ELDHO; SHARMA, V K (The Indian Journal of Agricultural Sciences, 2015)
Attractive peel colour and quality development in Kinnow (Citrus nobilis Lour x Citrus deliciosa Tenara) is a prime requisite for its fair market price. The objective of study was to find out the impact of canopy position, date of harvesting and nutrition on yield and quality of Kinnow mandarin. A field experiment was conducted in a four year old Kinnow orchard using factorial randomized block design with three replications. There were nine treatments comprised of various N, P, K levels and one control; two canopy positions (external and internal) and three harvesting dates (06.12.13, 26.12.13 and 16.01.14). Statistical analysis using SAS 9.3 software and Tukey's HSD test revealed the significance of various treatments, canopy positions and harvesting dates (P